Pengaruh Sistem Informasi Akuntansi Next Basis dan Pengendalian Internal Terhadap Kinerja Karyawan PT Surya Sinar Berlian di Kota Denpasar - SUPARSA, I KOMANG; YUNIASIH, NI WAYAN (Hita Akuntansi dan Keuangan, 2025)
T PT Surya Sinar Berlian is a distributor companny engagged in the distributions of herbal and pharmaceutical medicines in Denpasar City. PT Surya Sinar Berlian experienced quite a lot of problems, the first of which was in the administration section because it used a lot of manual systems which often caused human error. PT Surya Sinar Berlian in Denpasar. Thes populations in this study werre all employeess at PT. Surya Sinar Berlian Denpasar, totaling 53 people. The analysiss techniique used is multipled linear analyssis using SPSS. After implementing the employee performance instruments of PT. Surya Sinar Berlian in Denpasar City and internal control have a possitive and significcant effect on the performances of PT employeess. Surya Sinar Berlian in Denpasar City.